Pengaruh model pembelajaran predict-observe-explain (POE) terhadap berpikir kritis dan hasil belajar siswa pada materi sistem ekskresi kelas VIII SMPN 23 Makassar - Nurul Rahma Yanti; Andi Tenri Ola Rivai; Syamsul Syamsul (JURNAL BIOEDUKASI, 2025)
The teaching and learning process is faced with the challenge of low student learning outcomes. Contributing factors include misconceptions, difficulties in understanding science material, and a lack of learning models that actively involve students. Other factors such as time constraints, a lack of problem-solving stimulation, and other internal factors also affect students' critical thinking abilities and learning outcomes. The purpose of this study, to know: (1) critical thinking of students taught using the Predict-Observe-Explain (POE) learning model on excretory system material class VIII SMPN 23 Makassar, (2) learning outcomes of student taught using the Predict-Observe-Explain (POE) learning model on excretory system material class VIII SMPN 23 Makassar, (3) critical thinking taught without using the Predict-Observe-Explain (POE) learning model on exretory system material class VIII SMPN 23 Makassar, (4) learning outcomes of students thaught without using the predict-observe-explain (POE) learning model on excretory system material class VIII SMPN 23 Makassar,(5) the effect of Predict-Observe-Explain (POE) learning model on critical thinking of students on excretory system material class VIII SMPN 23 Makassar, (6) the effect of Predict-Observe-Explain (POE) learning model on student learning outcomes on excretory system material class VIII SMPN 23 Makassar.This study used a quasi-experiment with a non-equivalent control group design research design. The population in the study was two hundred and ninety-one students of class VIII of SMP Negeri 23 Makassar. There were a total of 86 people surveyed: 44 participated in the control group and 42 in the experimental class group. Sample determination was done by purposive sampling. The tools used as data collection are in the form of observation sheets, critical thinking ability tests and learning outcomes tests. Data analysis uses descriptive analysis and inferential analysis which includes homogeneity test, hypothesis testing and normality. The results showed that in critical thinking and student learning outcomes with a Sign value a 0.001. So that in this study there is a significant difference between critical thinking and learning outcomes of students taught without using the predict-observe-explain (POE) learning model and using the Predict-Observe-Explain (POE) learning model on excretory system material class VIII SMP Negeri 23 Makassar.